2010
DOI: 10.1111/j.1476-5381.2009.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of adenosine A2B receptors induces interleukin‐6 secretion in cardiac fibroblasts via the PKC‐δ–P38 signalling pathway

Abstract: Background and purpose: Inflammatory response and cytokine activation are markedly stimulated after myocardial infarction, and contribute to cardiac remodelling. Interleukin-6 (IL-6), a pro-inflammatory cytokine, has pleiotropic effects on cardiac remodelling. Adenosine, released by all cell types, binds to a class of G protein-coupled receptors to induce various cardiovascular effects. The aim of this work was to investigate whether activation of adenosine receptors, particularly A2B adenosine receptors, coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…In the literature there are reports indicating the presence of different adenosine receptor subtypes on immune cells (38) and cultured cardiac fibroblasts (39). We can speculate that adenosine might play an additional role in systemic hypertension mediating inflammatory cell recruitment and/or vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are reports indicating the presence of different adenosine receptor subtypes on immune cells (38) and cultured cardiac fibroblasts (39). We can speculate that adenosine might play an additional role in systemic hypertension mediating inflammatory cell recruitment and/or vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, TNF-α or NF-κB (tissue mRNA, proteome profiler/ELISA and WB) were not clearly involved. However, the release of IL-6 and IL-8 is known to be linked to p38 signaling (19,20) and has so far not been reported for reflux esophagitis.…”
Section: Factor Analysis Identified Cinc1-3 Mip-1/3` Mig Rantes Anmentioning
confidence: 99%
“…This receptor fickleness was confirmed by Feng et al (2009) in the current edition of the British Journal of Pharmacology. They examined production of the proinflammatory cytokine interleukin-6 (IL-6) by mouse cardiac fibroblasts following exposure to 5′-(N-ethylcarboxamido) adenosine (NECA), a potent, albeit not selective, A2b receptor agonist.…”
mentioning
confidence: 62%
“…Clearly IL-6 production by cardiac fibroblasts was greatly influenced by stimulation of A2b receptors. When Feng et al (2009) studied the downstream signalling they found involvement of Gq and not Gs. Pretreatment with either the cAMP-competitive analog Rp-cAMPS or 1 of two protein kinase A (PKA) inhibitors, H-89 or KT 5720, before exposure to NECA failed to block NECAinduced IL-6 production.…”
mentioning
confidence: 99%